2004
DOI: 10.1364/opex.12.000249
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optical scattering properties of highly-scattering media in optical coherence tomography images

Abstract: Abstract:We developed a new algorithm that fits optical coherence tomography (OCT) signals as a function of depth to a general theoretical OCT model which takes into account multiple scattering effects. With use of this algorithm, it was possible to extract both the scattering coefficient and anisotropy factor from a particular region of interest in an OCT image. The extraction algorithm was evaluated against measurements from an integrating sphere on a set of tissue phantoms and yielded valid results. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 20 publications
4
150
0
Order By: Relevance
“…According to the OCT signal formation theory [16], the slope of the OCT signal carries information about the scattering properties of the medium under study, such as scattering and absorption coefficients. Several research groups [17][18][19] have reported the possibility of determining the optical properties of scattering media by the OCT technique using rather complicated theories of OCT signal formation. This approach was used to monitor the glucose level in biotissues in vivo [20,21].…”
Section: Scattering Properties Of Cytoplasmmentioning
confidence: 99%
“…According to the OCT signal formation theory [16], the slope of the OCT signal carries information about the scattering properties of the medium under study, such as scattering and absorption coefficients. Several research groups [17][18][19] have reported the possibility of determining the optical properties of scattering media by the OCT technique using rather complicated theories of OCT signal formation. This approach was used to monitor the glucose level in biotissues in vivo [20,21].…”
Section: Scattering Properties Of Cytoplasmmentioning
confidence: 99%
“…The research of quantitative determination using OCT has been reported [14][15][16][17] . And this improvement can identify the types which are not recognized by OCT structure.…”
Section: Optical Coherence Tomography (Oct) Is a Low Coherencementioning
confidence: 99%
“…The details of this model have been described by Levitz [14][15][16][17] . In brief, the algorithm consists of several steps: first, the transverse region of interests (ROIs) with thirty curves fitting attempts per ROI from every de-background image is selected; then these adjacent a-scans are averaged along the lateral direction to yield an attenuate curve, where the fitted length is chosen to be 0.23 mm (80 pixels).…”
Section: Calculation Of the Optical Parametersmentioning
confidence: 99%
“…Knüttel et al expanded Tearney's focus tracking method to measure depth-resolved changes of the refractive index [131]. Based on the model by Thrane et al relating the OCT signal strength to scattering [132], Letvitz et al extracted the scattering coefficient and the effective anisotropy factor from OCT A-scans [133], and Turchin et al developed an algorithm to derive the scattering coefficients of multi-layer samples [134]. Both methods aimed for the characterization of different pathologic states in tissue samples.…”
Section: Measurement Of Bulk Optical Propertiesmentioning
confidence: 99%
“…Ex vivo measurements demonstrated the ability to distinguish different tissue structures [49] and plaque types [133,178], followed by in vivo studies aiming at the identification of vulnerable atherosclerotic plaques [179][180][181]. OCT can quantify typical characteristics such as the fibrous cap thickness [182], presence of lipid [135], or macrophage infiltration [183].…”
Section: Cardiologymentioning
confidence: 99%